The siege of macindaw eaudiobook - Flanagan, John (Ranger's Apprentice, 2019)
The international bestselling series with over 5 million copies sold in the U.S. alone !   After years as a Ranger's apprentice, Will is now the protector of his first fief. Not long into his service, everything that can go wrong does: Keren, a renegade knight, has taken over Castle Macindaw, a strategic gateway to the North—poisoning the royal family in the process—and is holding Will's friend Alyss captive. The situation grows direr when Will uncovers Keren's secret alliance with the Scotti, who have plans to plunder Araluen. Time is of the essence, and Will must recruit a motley crew to rescue Alyss and reclaim Castle Macindaw—before the Scotti can make it their own. This New York Times bestselling series maintains its breathless pace in this newest installment. Perfect for fans of J.R.R. Tolkien’s Lord of the Rings, T.H. White’s The Sword in the Stone, Christopher Paolini’s Eragon series, and George R. R. Martin’s Game of Thrones/A Song of Ice and Fire series.